Exploring park–people conflicts in Colombia through a social lens - Pourcq, K. de; Thomas, E.; Elias, Marlène; Damme, P. van (Cambridge University Press, 2019)
Natural resource-related conflicts between local communities and nation states can be extremely destructive. Worldwide, interest is growing in gaining a better understanding of why and how these conflicts originate, particularly in protected areas inhabited by local communities. The literature on local attitudes towards and perceptions of park conservation and park–people conflicts is quite extensive. Studies have examined the socioeconomic and geographical determinants of attitudes to protected areas. However, the role of such determinants in the experience of park–people conflicts has received considerably less attention. Drawing on 601 interviews with people living in or near 15 Colombian national protected areas (NPAs), we examine the socioeconomic and geographical variables that are most influential in people’s experience of conflict related to restricted access to natural resources. We find that the experience of this type of conflict is largely explained by the NPA where a person resides, pursuit of productive activities within the NPA, previous employment in NPA administration, gender and ethnicity. We recommend implementing socially inclusive conservation strategies for conflict prevention and resolution in Colombia’s NPAs, whereby both women and men from different ethnic groups are engaged in design and implementation.